2013
DOI: 10.1007/s10551-013-1806-z
|View full text |Cite
|
Sign up to set email alerts
|

The Means to Justify the End: Combating Cyber Harassment in Social Media

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Every day, people use millions of online communities to get the news [25,71,74], for support [1,3,20,21,62,63,72], for entertainment [12,46], to discuss with others [16,68,78], to compete with others [2,60], and many other purposes. Some aspects of communities have been tied to specific societal harms, including distribution of misinformation [4,34,39,40,69,79], harassment and bullying [10,11,38,44,50,51,53,70,76], and increasing polarization [7-9, 28, 33, 61]. However, a recent survey of reddit users found that the academic community has focused relatively less on the broader values that still are of great importance to community members, such as quality of content and diversity of the community [75].…”
Section: Introductionmentioning
confidence: 99%
“…Every day, people use millions of online communities to get the news [25,71,74], for support [1,3,20,21,62,63,72], for entertainment [12,46], to discuss with others [16,68,78], to compete with others [2,60], and many other purposes. Some aspects of communities have been tied to specific societal harms, including distribution of misinformation [4,34,39,40,69,79], harassment and bullying [10,11,38,44,50,51,53,70,76], and increasing polarization [7-9, 28, 33, 61]. However, a recent survey of reddit users found that the academic community has focused relatively less on the broader values that still are of great importance to community members, such as quality of content and diversity of the community [75].…”
Section: Introductionmentioning
confidence: 99%
“…Different research areas have addressed the question of morality in the digital age. That is, contributions have been made, for example, in the fields of public health (Laer, 2014), business strategy (Ferreira et al, 2017), political sciences (Brady et al, 2017), communication sciences (Valenzuela et al, 2017), and psychology (Garcia and Sikström, 2014). We aimed to identify contributions from different research fields on social media’s relationship with moral behaviors, judgments, reasoning, intuitions, emotions, and self-views.…”
Section: Objectives Of This Scoping Reviewmentioning
confidence: 99%
“…Perceptions of the influence of social media have changed significantly in recent years (Pescott, 2020; Charoensukmongkol, 2018; van Zoonen et al , 2016; Chou and Edge, 2012), shifting from seeing only the bright side to recognizing negative, dark effects of social media (Dhir et al , 2021). Well-known dark sides of social media are fake news , which unconsciously influences people’s beliefs (Allcott and Gentzkow, 2017) or destroys companies’ reputations, cyberstalking (Winkelman et al , 2015; van Laer, 2014), trolling (Hannan, 2018) and privacy concerns , especially regarding tech-companies (Malik et al , 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%